Foreign Wars and Domestic Prejudice: How Media Exposure to the Israeli-Palestinian Conflict Predicts Ethnic Stereotyping by Jewish and Arab American Adolescents - Huesmann, L. Rowell (2012)
This study was based on the theory that adolescents view scenes of violent ethnic conflicts in the mass media through the lens of their own ethnicity, and that the resulting social-cognitive reactions influence their negative stereotypes about similar ethnic groups in their own country. We interviewed 89 Jewish and 180 Arab American high school students about their exposure to the Israeli-Palestinian conflict, their social cognitive reactions to it, and their stereotypes toward ethnic groups. Beyond the effects of ethnic identity, the degree to which adolescents identified with Israelis and Palestinians in the media was a key variable linking exposure to media depictions of the conflict and the implicit ethnic stereotypes they displayed about Jewish Americans and Arab Americans.